PROPOSAL OF A PROCEDURE FOR AUTOMATING AN INDUSTRIAL PROCESS USING PETRI NETS AS A FORMAL TOOL - Juan David Contreras; Ruth Edmy Cano Buitrón; José Isidro García Melo (Revista Politécnica, 2018)
Currently, industrial systems must adapt to changes in globalized markets in order to be competitive. In this context, automation is presented as a solution to ensure the efficiency and effectiveness of production. However, a correct specification of this kind of response is not a trivial task. This is due to the increase in the process dynamic complexity that involves personnel and technical resources of different nature as well as, risks derived from an incorrect solution definition. Thus, this article presents a structured process that considers the semantics of UML, Petri Nets as a modeling tools and automation standards to define the requirements, behavior and implementation of the system automation project. In order to assess the proposed approach, an application example was developed. Finally, the relevant contributions are stated in the context of the application.